Standar Kualitas dalam Budaya Organisasi: Integrasi Sistem Kualitas, Standardisasi, dan Penerapan ISO 9000 - Siska Putri; Himyar Pasrizal (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study critically examines the strategic role of quality standards in shaping organizational culture through the integration of quality management systems, standardization practices, and the implementation of ISO 9000. Adopting a descriptive qualitative approach, this research employs a comprehensive literature review of scholarly articles, academic books, and international standardization documents to develop a conceptual understanding of quality-driven organizational transformation. Data analysis techniques using thematic analysis. The findings reveal that quality management systems function as a foundational infrastructure in institutionalizing structured, consistent, and performance-oriented work practices. Standardization emerges as a pivotal mechanism for reducing process variability, enhancing operational efficiency, and reinforcing organizational discipline and compliance. The adoption of ISO 9000 provides a globally recognized framework that fosters transparency, accountability, and systematic quality governance, thereby embedding a culture of continuous improvement within the organization. The study also highlights the synergistic contribution of Total Quality Management (TQM) and Kaizen, which collectively promote participatory engagement, incremental innovation, and sustained process enhancement. This research has limitations because it uses the Systematic Literature Review (SLR) method, so it is hoped that future researchers will conduct research directly in the field, either at institutions or organizations.